Simulation and assessment of agricultural biomass supply chain systems - D. Pavlou; A. Orfanou; D. Bochtis; S. Tamvakidis; D. Aidonis (International Journal of Business Science & Applied Management (IJBSAM), 2016)
Agricultural biomass supply chain consists of a number of interacted sequential operations affected by various variables, such as weather conditions, machinery systems, and biomass features. These facts make the process of biomass supply chain as a complex system that requires computational tools, e.g. simulation and mathematical models, for their assessment and analysis. A biomass supply chain simulation model developed on the ExtendSim 8 simulation environment is presented in this paper. A number of sequential operations are applied in order biomass to be mowed, harvested, and transported to a biorefinery facility. Different operational scenarios regarding the travel distance between field and biorefinery facility, number of machines, and capacity of machines are analyzed showing how different parameters affect the processes within biomass supply chain in terms of time and cost. The results shown that parameters such as area of the field, travel distance, number of available machines, capacity of the machines, etc. should be taken into account in order a less time and/ or cost consuming machinery combination to be selected.
Keywords: 650; agricultural biomass; supply chain management; simulation model; agricultural machinery; operations management